PROTECTION OF THE HAIR CELLS FROM THE OTOTOXIC EFFECT OF STREPTOMYCIN - Aman, Maharjan; Muzammal Hoque, Mollah; Shashi Bhushan, Yadav; Fathima, M.A.A; Naagrathna, P.K.M. (International Journal of Ayurveda and Pharma Research, 2015)
Ototoxicity is the property of being toxic to the ear (oto), specifically the cochlea or auditory nerve and sometimes the vestibular system; it is commonly medication-induced. It has long been known that the major irreversible toxicity of aminoglycosides is ototoxicity. In many developing countries, where drugs such as the aminoglycosides are frequently prescribed to treat pneumonia, diarrhoea, and tuberculosis, the incidence of ototoxicity is high. Physicians in practice need to recognize that ototoxic drugs can cause significant auditory and in many instances, poorly recognized, vestibular toxicity. Aminoglycosides can cause eighth cranial nerve damage, resulting in vestibular and/or auditory toxicities. Aminoglycosides appear to generate free radicals within the inner ear, with subsequent permanent damage to sensory cells and neurons, resulting in permanent hearing loss. Two mutations in the mitochondrial 12S ribosomal RNA gene have been previously reported to predispose carriers to aminoglycoside-induced ototoxicity. As aminoglycosides are indispensable agents both in the treatment of infections and Menieres disease, a great effort has been made to develop strategies to prevent aminoglycoside ototoxicity. Efforts have been made against streptomycin toxicity using corticosteroid and Caffeic acid phenethyl ester. Chemicals are being evaluated for their ability to prevent ototoxicity and that might be prescribed in tandem with ototoxic drugs in the future. Investigators are also studying methods of hair-cell and nerve-cell regeneration.